Jus Wheatgrass (Rumput Gandum) untuk Mengurangi Efek Kemoterapi - Alfhy Septiana Ningsih; Dewi Gayatri; Elly Nurachmah; Allenidekania Allenidekania (Jurnal Keperawatan Silampari, 2022)
This study aims to describe and analyze the benefits of wheatgrass in reducing the effects of chemotherapy. The design of this research is a systematic narrative review. Six scientific databases were used to obtain relevant sources dealing with specific issues related to wheatgrass in reducing the effects of chemotherapy, namely Pubmed, Ebsco, Sage Journals, Clinical Key, Scopus, and Pro-quest. The study results found 655 articles, and six articles were relevant and qualified. The use of wheatgrass juice turned out to have a significant effect on treating cancer patients in reducing the impact of chemotherapy and providing alternative options for reducing the effects of chemotherapy. In conclusion, wheatgrass can increase hemoglobin and platelet levels, contain antineoplastic compounds, suppress EMT in hypoxia, and can improve the performance of P53 cells in performing apoptosis. Keywords: Cancer, Chemotherapy, Wheatgrass